Characterization of Streptomyces spp. from rice fields as a potential biocontrol agent against Burkholderia glumae and rice plant growth promoter - Ngalimat, Mohamad Syazwan; Mohd Hata, Erneeza; Zulperi, Dzarifah; Ismail, Siti Izera; Ismail, Mohd Razi; Mohd Zainudin, Nur Ain Izzati; Saidi, Noor Baity; Yusof, Mohd Termizi (Multidisciplinary Digital Publishing Institute, 2021)
The usage of plant growth-promoting (PGP) Streptomyces to improve plant growth is an alternative to existing strategies of chemical fertilizers that commonly caused environmental pollution. The aim of this study was to isolate and characterize PGP Streptomyces from Malaysian rice fields with antagonistic activity against Bacterial Panicle Blight disease in rice caused by Burkholderia glumae. A total of 50 bacterial isolates were recovered from the soil, rhizosphere, and endosphere; 22% showed antagonistic activity against B. glumae. Molecular identification using 16S rRNA amplification and phylogenetic tree analyses revealed that the antagonistic isolates belonged to the genus Streptomyces. Among the antagonistic isolates, Streptomyces sp. TBS5 (26.35 ± 0.14 mm) demonstrated the most antagonistic activity (p < 0.05) against B. glumae. Through API® ZYM analysis, the antagonistic isolates were revealed to have phosphoric hydrolase, ester hydrolase, peptide hydrolase, and glycosidase activities that play a crucial role in plant growth promotion. The antagonistic isolates demonstrated the highest (80%) PGP traits including able to fix nitrogen and solubilize phosphate, as well as produce siderophore and indole-3-acetic acid. Plant growth promotion assay under laboratory and greenhouse conditions were analyzed with the treatment of rice, Oryza sativa, seeds with the antagonistic isolates. Seeds treated with Streptomyces sp. TBS5, JAS2, R2-7, and TKR8 showed improvement in vigor index by more than 100% compared to water-treated control plants under both conditions. Augmentation of root length showed an overall increment of more than 101.5% under laboratory condition and 151.9% under greenhouse condition using Streptomyces sp. TBS5, JAS2, R2-7, and TKR8 treatments. Results suggest that Streptomyces sp. TBS5, JAS2, R2-7, and TKR8 are a good candidate to be developed as both biocontrol agent against B. glumae and PGP agent in rice.